Impact of social imageability on intensity of passive social interaction along designated paths within urban parks in Kuala Lumpur, Malaysia - Tahroodi, Faezeh Mohammadi (2018)
Underutilized parks in Kuala Lumpur showed the fact that the design of these areas could not serve as a responsive social public space. However, Kuala Lumpur seeks to establish itself as one of the top twenty most imageable cities in the world by the year 2020. Therefore, there is an emphasis on developing urban design guidelines toward regenerating existing urban parks and also developing new parks to meet this aim. The aim of the study is to enhance social interaction through examining the impact of social imageability attributes comprising legibility, accessibility, sensation of orientation and sensation of center on the Intensity of Passive Social Interaction (IPSI) within path structures of Lake Garden Park (LGP) and Titiwangsa Lake Park (TLP) located in Kuala Lumpur city center. A mixed method research strategy is adapted to develop a framework to predict the Intensity of Passive Social Interaction (IPSI) through determining the correlation among social imageability attributes. Accordingly, experiential landscape maps were produced and interpreted to determine the levels of legibility of the parks. Then, integration analysis and gate observation were used to ascertain the levels of accessibility and the Intensity of Passive Social Interaction (IPSI) respectively. Finally, the study applied 330 photo survey questionnaires from urban park users to determine, the extent of sensation of orientation and, the extent of sensation of center. The study hypothesized that there is a significant relationship among social imageability attributes within path structures of urban parks. Both quantitative and qualitative data were related to generate the findings of the research. The correlation value of more than 0.6 for each of two social imageability attributes verifies that these attributes are highly correlated with each other. This association highlights the relevance of social imageability in influencing place experience within public realm. Therefore, it is recommended that the design of the designated paths with landmarks and possible views to be enriched, thus increasing the experience of these paths via activities. This could be achieved by locating activity nodes at the proximity of designated paths. It is also important to allocate active and accessible land uses at direct visual access of park users. It is also suggested that urban designers to empower activity nodes with sensation of center through offering diversity of activities and visual attractiveness and providing comfortable places to sit, spend time, meet friends and interact with strangers. The study proposes to apply proper distance for each designated path (25 to 100 meter) providing eye contact among people, along with avoiding using sharp angles. In addition, boundary of urban parks should be made permeable. A multiple linear regression framework that predicts the Intensity of Passive Social Interaction (IPSI) indicates that the enhancement of accessibility value, sensation of center and sensation of orientation will increase the intensity of dynamic social activities generating passive eye contact among urban park users. The findings of this study contribute in making urban places more imageable for social interaction to take place more intensely and frequently. Thus encourage the users to experience the entire urban park with ease and enjoyment.